Molecular imprinted polymers based on magnetic chitosan with different deep eutectic solvent monomers for the selective separation of catechins in black tea. Issue 15 (9th March 2018) - Ma, Wanwan; Dai, Yunliang; Row, Kyung Ho
Abstract: Two types of molecular‐imprinted polymers‐based magnetic chitosan with facile deep eutectic solvent‐functional monomers (Fe3 O4 ‐CTS@DES‐MIPs) were synthesized and applied as adsorbents in magnetic solid‐phase extraction (MSPE) for the selective recognition and separation of (+)‐catechin, (−)‐epicatechin, and (−)‐epigallocatechin gallate in black tea. The obtained Fe3 O4 ‐CTS@DES‐MIPs were characterized by Fourier transform infrared spectroscopy and field emission scanning electron microscopy. The selective recognition ability was examined by adsorption experiments. The actual amounts of (+)‐catechin, (−)‐epicatechin, and (−)‐epigallocatechin gallate extracted from black tea using Fe3 O4 ‐CTS@DES‐MIPs by the MSPE method were 13.10, 6.32, and 8.76 mg/g, respectively. In addition, the magnetic Fe3 O4 ‐CTS@DES‐MIPs showed outstanding recognition and selectivity. Therefore, it can be used to separate bioactive compounds from black tea. The new‐type of DES adopted as the functional monomer in this paper provides a new perspective for the recognition and separation of bioactive compounds.